Epidemiological characteristics of heart transplant recipients in Peru 2010-2020 - Polo Lecca, Gracia del Carmen (2021)
Objective. To evaluate the epidemiological, clinical, surgical, pathological characteristics and outcomes in the follow-up of heart transplant recipients at the National Cardiovascular Institute during 2010-2020. Material and methods. A retrospective descriptive study was performed by reviewing the medical records of patients undergoing heart transplantation at a national referral center, describing the clinical, surgical, laboratory, pathology characteristics and survival of patients up to 10 years of follow-up. Results. Eightysix patients were transplanted in 10 years, the median age was 41 years (RIQ 28-56), being predominantly male (66.3%). The three leading causes of indication for heart transplantation were: dilated cardiomyopathy (48.9%), ischemic heart disease (17.4%), and myocarditis (6.9%). Total ischemia time was 160 minutes (RIQ 129.7-233.5). Survival at one, five, and ten years was 84.8%, 73.6%, and 65.7% respectively. The main cause of death was non-cardiac: infectious (39.1%) and of unknown origin (26%). Conclusions. The main etiology of heart failure in heart transplant recipients in Peru in recent years was nonischemic dilated cardiomyopathy. We observed that the survival rate was similar to that of international registries; however, the rate of mortality due to infectious causes and death of unknown origin is high, which poses a challenge in the management of post-transplant patients.